(untitled) - Norman, E. H. (New York, 1975)
Contents: 1. Japan's emergence as a modern state, 2. Feudal background of Japanese politics, 3. E.H. Norman: A bibliography
Keywords: Japan,Nhật Bản; History,Lịch sử